2012
DOI: 10.3233/ch-2011-1520
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific regulation of acetylcholinesterase expression under inflammatory conditions

Abstract: Acetylcholine (ACh) has been shown to exert an anti-inflammatory function by downmodulating the expression of pro-inflammatory cytokines. Its availability can be regulated at different levels, namely at its synthesis and degradation steps. Accordingly, the expression of acetylcholinesterase (AChE), the enzyme responsible for ACh hydrolysis, has been observed to be modulated in inflammation. To further address the mechanisms underlying this effect, we aimed here at characterizing AChE expression in distinct cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Recently, inflamed cells and tissues were found to present a greater amount of ACh, (Wessler and Kirkpatrick, 2008), accompanied by AChE expression (de Oliveira et al, 2012) and activity, compared to the healthy ones. A similar increase of AChE activity was found in wound healing tissues (Falugi et al, 1994).…”
Section: Non-neuromuscular Roles Of the Molecules Related To The Cholmentioning
confidence: 99%
“…Recently, inflamed cells and tissues were found to present a greater amount of ACh, (Wessler and Kirkpatrick, 2008), accompanied by AChE expression (de Oliveira et al, 2012) and activity, compared to the healthy ones. A similar increase of AChE activity was found in wound healing tissues (Falugi et al, 1994).…”
Section: Non-neuromuscular Roles Of the Molecules Related To The Cholmentioning
confidence: 99%
“…Furthermore, Genever and his colleagues demonstrated that AChE is a novel osteoblast-derived mediator of cell-matrix interactions [14] [15] . Although AChE is also expressed in macrophages and osteoclasts as well [16] [17] , the function of AChE in osteoclasts has not been examined before.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that AChE can become also expressed in the course of its inhibition or stress conditions (Darreh-Shori & Soininen, 2010 ; de Oliveira et al , 2012 ). The improvement in the level of low molecular weight antioxidants reported here is beneficial for keeping the homeostasis of basic reactive oxygen species.…”
Section: Resultsmentioning
confidence: 99%